The Correlation between Vitamin D Intake and Quality of Life in the 17-35 Age Group - Suci Prasetyo; Veronika Maria Sidharta; Komang Ardi Wahyuningsih; Yunisa Astiarani; In Sil Huh (Faculty of Public Health, Hasanuddin University, Makassar, 2022)
Vitamin D testing increased significantly during the Coronavirus Disease-19 (COVID-19) pandemics due to its role in regulating the immune system. Therefore, vitamin D deficiency is associated with susceptibility to various diseases that may affect the quality of life regarding physical health, psychological well-being, social and environmental aspects. The study aimed to determine whether there is an association between vitamin D intake and quality of life in the 17 to 35-year-old age group. A cross-sectional study was conducted from April to November 2021. The sample consisted of students from the School of Medicine and Health Sciences Atma Jaya Catholic University of Indonesia, and their relatives in the same age group, who were selected using a consecutive sampling. Vitamin D intake was measured using Vitamin D Estimation Only - Food Frequency Questionnaire (VIDEO-FFQ). At the same time, the quality of life was assessed using the World Health Organization Quality of Life (WHOQOL)-BREF questionnaire. Data analysis was performed using the Chi-square test. Of the 127 respondents, the results showed that most of respondents had inadequate vitamin D intake and good quality of life (68.50%;59.10%). The highest mean of the four quality of life domains belongs to the environmental domain (3.94) with a standard deviation (SD) of ± 0.83. Data analysis showed no significant correlation between vitamin D intake and quality of life (p>0.05). The conclusion shows that there was no correlation between vitamin D intake and quality of life in the 17–35-year age group.